MATHEMATICAL MODELING OF NATURAL PHENOMENA - Corrêa Veloso dos Santos, Felipe; Fernandes da Silva, Edivaldo; Mesquita Vaz, Tatiane (Journal of Interdisciplinary Debates, 2024)
The comprehension of the phenomena that pervade our world is a pursuit that extends beyond the confines of conventional disciplinary boundaries. In recent decades, mathematical modeling has emerged as a powerful tool for elucidating the enigmas of these intricate phenomena, irrespective of their provenance in the exact sciences, biology, geography, or other domains of human knowledge. In this sense, the objective of this study was to review and recover concepts inherent in modeling with a focus on interdisciplinarity. From this comprehensive review, it can be inferred that by exploring examples in various disciplines, the crucial role that mathematical modeling plays in understanding and predicting complex phenomena becomes evident. Through the analysis of the various techniques and approaches presented, it is notable how mathematical modeling transcends disciplinary boundaries, providing unique insights and powerful tools for exploring the natural world and the interactions that occur within it.